The prospect of using ozone-safe refrigerants with low global warming potential in scroll compressors. Research and practice of using R744 and R290. Part 2 - V. A. Pronin; A. V. Kovanov; E. A. Kalashnikova; V. A. Tsvetkov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2022)
Scroll compressors currently operate successfully on various natural refrigerants, among which the most popular are propane R290 and carbon dioxide R744. This is due to the performance characteristics of the refrigerants studied in the previous article. However, the key to improving scroll technology further adapting or creating new models of compressors is a detailed study of the thermophysical and thermodynamic properties of propane and CO2. The article analyzes the possible areas of application of R290 and R744 from the point of view of the influence of their properties on work processes and the question of the need for structural changes to the compressor. The question of the relationship between the properties of hydrofluorocarbons and natural refrigerants is considered, as well as the possibility of using the theory of thermodynamic similarity to solve it. Data on commercially available scroll compressors operating on natural refrigerants have been taken into account in terms of their advantages and disadvantages. Thus, conclusions are drawn about the prospects for the use of R290, R744 and current research directions for expanding the scope of scroll compressors from the point of view of the general problem of using ozone-friendly refrigerants with a low global warming potential.